Debutant Teachers’ Perceptions of the Benefits of the Discussion Method in University Studies - Valantinaitė, Ilona; Sederevičiūtė-Pačiauskienė, Živilė; Asakavičiūtė, Vaida (Journal of Education Culture and Society, 2025)
Aim. This study investigates how first-year Ph.D. students who lack prior teaching experience perceive the role of virtual discussions in developing their teaching-related competencies, including pedagogical and communicative skills.Methods. Data collected from debutant Ph.D. students at three universities in 2021, 2022, and 2023 was analysed using a phenomenographic approach. The Community of Inquiry (CoI) framework (Garrison et al., 2000) guided the design of discussion tasks and the analysis of students' experiences, enabling a deeper understanding of the value students place on virtual discussions.Results. The analysis identified four primary benefits of virtual discussions in the study process: (1) as an interactive study method, (2) as a medium for enhancing clarity in thought articulation, (3) as a tool for developing topic-specific discussion skills, and (4) as a way to foster personal growth in communicative competencies. These benefits contribute to Ph.D. students' preparedness to engage in collaborative academic environments and build essential interpersonal skills.Conclusions. Even though the discussion method and the discussion are treated as an "unusual study" format, the discussion method is not familiar to debutant teachers with no teacher training background. If organised correctly, the discussion increases students' social and cognitive presence and fosters critical thinking and empathy. Virtual discussions serve as a valuable learning tool and contribute to developing valuable skills and enhancing participants' academic and personal growth. The findings suggest that incorporating structured virtual discussions as an instructional method in synchronous higher education settings could be beneficial for developing Ph.D. s